Measurement Properties of Aerobic Capacity Measures in Neuromuscular Diseases: A Systematic Review - Tim Veneman; Fieke Sophia Koopman; Joost Daams; Frans Nollet; Eric Lukas Voorn (Medical Journals Sweden, 2022)
Objective: To systematically evaluate the measurement properties of aerobic capacity measures in neuromuscular diseases. Data sources: MEDLINE, EMBASE, SportDiscus and Web of Science Conference Proceedings Citation Index - Science were systematically searched from inception until 30 June 2021. Study selection and data extraction: Screening, data extraction, risk of bias assessment and quality assessment were performed by 2 independent researchers. Studies were included if they evaluated measurement properties of aerobic capacity measures in adults with neuromuscular diseases. Risk of bias was assessed using the COnsensus based Standards for the selection of health status Measurement INstruments (COSMIN) checklist. Results were pooled and the quality of the evidence was determined using a modified Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach. Data synthesis: Nine studies including 187 participants were included in this review. Low quality of evidence was found for sufficient content validity of peak oxygen consumption through maximal exercise testing. Criterion validity of 4 out of 7 different measures to predict peak oxygen consumption was sufficient; however, quality of evidence was low or very low for all measures. No studies were found evaluating reliability or responsiveness. Conclusion: There was a lack of high-quality studies with sufficiently large sample sizes that evaluated the measurement properties of aerobic capacity measures in neuromuscular diseases. LAY ABSTRACT Aerobic capacity (or cardiovascular endurance) is an important outcome measure in exercise intervention studies and pharmacological trials in neuromuscular diseases. To establish the effects of these interventions it is important to use outcome measures with good measurement properties. This means that outcome measures are accurate (valid), repeatable (reliable) and able to detect change over time (responsive). The aim of this study was to review the scientific literature regarding the measurement properties of aerobic capacity measures in neuromuscular diseases. Nine small studies (4-44 participants) reporting on the validity of 8 aerobic capacity measures were found. Five of these measures were judged as valid, but the quality of evidence was low. There were no studies evaluating reliability and responsiveness. Taken together, these results were considered insufficient to make recommendations. High-quality studies, with more participants and a focus on reliability and responsiveness, are required.